SYNTHESIS OF THE ZSM-5 ZEOLITE WITH MIXTURES BINARY OF TETRAETHYLAMMONIUM HYDROXIDE AND AMINES AS ORGANIC STRUCTURE DIRECTING AGENTS - Diogo Pimentel de Sá da Silva; Bruno José Barros da Silva; Antonio Osimar Sousa da Silva (The Journal of Engineering and Exact Sciences)
Among the microporous materials used in heterogeneous catalysis, zeolites have become promising due to the relevant physicochemical and catalytic properties. Noteworthy is the zeolite ZSM-5 used as a catalyst in reactions in the areas of petrochemical and fine chemistry, such as cracking, isomerization, alkylation and aromatization reactions of olefins.  In view of this, the objective of this work was to synthesize the ZSM-5 zeolite, through binary mixtures of tetraethylammonium hydroxide (TEAOH) and different amines (n-butylamine, isobutylamine and diisobutylamine) acting as organic structure directing agents (SDA's). X-ray diffractometry indicated that only the reaction system containing TEAOH and n-butylamine provided the achievement of highly crystalline ZSM-5 and without competing phases. The nitrogen adsorption-desorption isotherms indicated that a material with a high surface area (329 m2·g-1) and pore volume (0.26 cm3·g-1) was obtained. Thus, it was possible to identify a new synthesis route in obtaining the ZSM-5 zeolite.